IMPLEMENTATION OF MAINTENANCE STRATEGY AND ASSET HEALTH MONITORING ON UNDERGROUND GBC PRODUCTION LOADER - David Siregar, Sahala
Asset Health Monitoring (AHM) is a new maintenance strategy developed at PT. Freeport Indonesia. One of the AHM strategy is oil analysis. This study aims to develop a degradation state of existing condition of major component in GBC R1600 Loader. The level of severity on oil analysis gives the indicator of severity level related to the health of its components. The study utilizes an Ordinal Logistic Regression method, to develop the category of degradation state. This methodology helps to identify and measure the severity of degradation state based on the wear rate, contamination, and deterioration of oil analysis parameters. The degradation state developed are 1) No Action Required, 2) Monitor Compartment, 3) Action Required. The additional category is 4) Urgent Action Required. The findings will provide new understanding of degradation state level of oil analysis. Maintenance activity such as time-based preventive maintenance, is succeeded to decrease the degradation state to the lower level. Lack of maintenance activity resulting in constant or increasing the degradation state severity. Degradation State of oil analysis will be supported by real-time categorial data of PLE (Product Link Elite) data. These datas are sensor readings related with pressure, temperature, flows, voltage, etc. The PLE datas will support the oil analysis degradation state and help maintenance division in the decision-making process. The AHM implementation requires RCM (Reliability Centered Maintenance) Department and Maintenance Dispacther to regularly monitor the health status of equipment and give analysis both to the operation underground division and maintenance division. The study finding is helping Operation Maintenance Division to address the issue related degradation state quicker to maintain the degradation. This quick response of intervention will help Operation Maintenance to maintain its major component before catastrophic failure happened. Binding policy such as SOP between underground division and maintenance division is needed tohave the best intervention program and action needed related with the health condition. Operator scorecard and maintenance staff KPI need to be the binding commitment for AHM to be succeed. Targer PA of R1600 Loader Minegem will be achieved by maintaining AHM of major component. By Implementing AHM, R1600 Minegem can achieve the availability target and major component can achieved its expected life.